Rapidly Progressing Osteomyelitis of the Mandible. (18th November 2013) - Kusuyama, Yukiko; Matsumoto, Ken; Okada, Shino; Wakabayashi, Ken; Takeuchi, Noritami; Yura, Yoshiaki
Abstract : Acute osteomyelitis exists as a refractory disease even now, which usually exhibits systemic symptoms such as fever or malaise and local redness or swelling. The present paper describes a case of acute osteomyelitis of the mandible that was rapidly progressing without typical symptoms. The patient had liver cirrhosis, which should be one of the systemic factors that affect immune surveillance and metabolism. Actinomycotic druses and filaments were detected from the sequestrum. These were considered to play a role in the rapid progression of osteomyelitis without typical symptoms. There has been no evidence of local recurrence 24 months after surgery.